Impact of Institutional Ownership, Debt to Equity Ratio, and Current Ratio on Stock Prices in Indonesian Transportation Companies (2017–2023) - Elly Sholihah; Santi Damayanti (Komunitas Dosen Indonesia, 2025)
This study examines the effect of Institutional Ownership (IO), Debt to Equity Ratio (DER), and Current Ratio (CR) on the stock prices of transportation companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2023. Using a quantitative methodology with a descriptive and verificative approach, the research analyses 49 financial statements from selected transportation firms. To test the relationships among the variables, multiple linear regression analysis, the coefficient of determination test, product moment correlation coefficient test, and classical assumption tests were conducted, including F-tests and t-tests for hypothesis testing. Data processing was performed using SPSS software version 21.0. The partial test results reveal that IO negatively impacts stock prices, while the DER also has a negative effect. In contrast, the CR does not significantly influence stock prices. However, based on the simultaneous test results, IO, DER, and CR together have a significant impact on stock prices. These findings suggest that capital structure and ownership composition play a crucial role in determining stock valuation in the transportation sector, while short-term liquidity does not appear to be a major influencing factor.